Gut microbiota regulate atherosclerosis via the gut-vascular axis: a scoping review of mechanisms and therapeutic interventions - Zhang, Dezhi; He, Xiaoqing; Shi, Yewei; Chen, Xinyue; Yu, Kai; Wang, Shuang (Frontiers in Microbiology, 2025)
BackgroundAtherosclerosis (AS) is a chronic inflammatory and metabolic disease, and advancements in its treatment have long been hampered by the complexity of its underlying mechanisms. The newly proposed “gut-vascular axis” theory holds promise for systematically elucidating the interactions between gut microbiota (GM) and vascular homeostasis. This provides a novel research framework for formulating precise preventive and therapeutic strategies against AS.ObjectiveTo explore the mechanisms by which GM and their metabolites regulate AS via the gut-vascular axis, and the potential application of intervention strategies targeting this axis in the prevention and treatment of AS.MethodsFollowing the methods of a scoping review, we searched the databases Cochrane Library, Embase, PubMed and Web of Science, and the search period was from January 1, 2014, to July 25, 2024. Two researchers individually reviewed the basic characteristics of the included studies.ResultsA total of articles were retrieved, identified 3556 articles and 192 of which were ultimately included in the study. The results are divided into three main sections, including the impact of GM and gut microbial metabolites (GMMs) on AS, and how various intervention factors can influence AS by influencing the composition of the GM.ConclusionBased on the gut-vascular axis theory, a multi-target combined intervention strategy has been proposed, encompassing probiotics/prebiotics regulation and precise nutritional interventions, thereby establishing novel approaches for AS prevention and treatment. Future research should prioritize the integration of artificial intelligence (AI) with multi-omics technologies to comprehensively decipher the interaction mechanisms between microbial metabolic networks and vascular pathologies within the gut-vascular axis framework. This interdisciplinary approach will promote the advancement of AS management toward emerging personalized precision medicine.Systematic review registration10.17605/OSF.IO/X8WQM.